2020
DOI: 10.3390/bs11010002
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Abdominal Surgeon’s Personality: Exploring Common Traits in Western Populations

Abstract: The personality traits commonly seen in abdominal surgeons remains undefined, and its potential influence on decision-making and patient outcomes underexplored. This systematic review identified studies on abdominal surgeons who had undergone validated personality testing, with assessment of decision-making and post-operative patient outcomes. The study protocol was registered on PROSPERO (University of York, UK (CRD42019151375)). MEDLINE, Embase, PsycInfo and Cochrane Library databases were searched using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Colorectal surgeons had higher levels of emotional stability (even-temperedness) than the general population and possessed lower-than-average levels of agreeableness (tendency towards conflict), extraversion (tendency towards enthusiasm, assertiveness), and openness to experience (tendency towards fixed thinking, routine), with some support for our findings from a recent systematic review on abdominal surgeon personality (high levels of conscientiousness) 15 . Interestingly, female surgeons had lower levels of openness than male surgeons, differing from what is commonly found in the general population 35 , 36 .…”
Section: Discussionsupporting
confidence: 79%
“…Colorectal surgeons had higher levels of emotional stability (even-temperedness) than the general population and possessed lower-than-average levels of agreeableness (tendency towards conflict), extraversion (tendency towards enthusiasm, assertiveness), and openness to experience (tendency towards fixed thinking, routine), with some support for our findings from a recent systematic review on abdominal surgeon personality (high levels of conscientiousness) 15 . Interestingly, female surgeons had lower levels of openness than male surgeons, differing from what is commonly found in the general population 35 , 36 .…”
Section: Discussionsupporting
confidence: 79%
“…[21] A systematic review conducted in 2020 sought to include studies in which the personality of surgeons was assessed, and found two studies reporting on perioperative decision making and/or postoperative outcomes. [22] High scores for conscientiousness and openness affected decision making with respect to the choice between making an anastomosis or a stoma. [23] In a real-life setting, surgeons with high levels of 'constructive' and 'passive/defensive' personality styles had fewer adverse events in bariatric surgery than surgeons with other styles.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 systematic review sought to explore common traits in the abdominal surgeons' personality [ 14 ]. The authors found that surgeon specific factors influence decision‐making and proposed the Five Factor Model for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the personality factors of surgeons that affect their decisions are clearly important and relevant [ 14 ], this study aimed to elucidate the nurse, surgeon and patient preferences for temporary diverting ileostomies (TDI) and evaluate any discrepancies through a series of three clinical scenarios and delivered by standardised, supervised participant interview. The preferences were ascertained by the validated prospective measures of preference: standard gamble (PMPsg) and time trade off (PMPtto) instruments.…”
Section: Introductionmentioning
confidence: 99%